Hubungan Antara Penguasaan Sintaksis Dan Penguasaan Nahwu Terhadap Kemampuan Menulis Teks Bahasa Arab Pada Mahasiswa Jurusan Pendidikan Bahasa Arab IAIN Pontianak - Midyan Surya Ishak (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
The background of this study is lack of understanding student with Arabic thesis produced by students of Arabic Education department in IAIN Pontianak FTIK. Those problems arise because of the low understanding of the logical language rules between Arabic and Indonesian. This study was analyzed by calculating path analysis. Based on the results of the analysis, it can be concluded that: 1) there is no significant relationship between syntactic mastery and mastery of students majoring in PBA, path parameter coefficient between syntax and mastery of nahwu science of -0.148 with T-Statistics of 0.868 and P-Values amounting to 0.387, because P> 0.05, 2) there is a significant positive relationship between syntactic mastery and the ability to write Arabic student text because the path parameter coefficient value between the two variables is 0.524 with a T-statistic value of 3.626 and P-Values ??of 0 00, because P <0.05, 3) there was an insignificant relationship between the mastery of nahwu and the ability to write Arabic student text because it obtained the path parameter parameter coefficient between the two variables of 0.214 with a T-Statistical value of 1.2229 and P-Values ??of 0.221 , because P> 0.05, 4) there is a significant relationship between mastery of sint simultaneous axis with mastery of student writing skills because the total effect of Syntax mastery together with the influence of mastery variables on writing ability is 0.493 with T statistic of 3.197 with P-Values ??level of 0.002, because P-Values ??is <0.05, then H0 is rejected.